Penentuan Waktu Proses Produksi Menggunakan Metode Stopwatch Time Study (Studi Penelitian Balai Besar Perikanan Budidaya Laut Lampung) - Rizqi Wahyudi; Bayu Ajib Setiawan; Juniwati Juniwati (Universitas Teuku Umar, 2024)
The province of Lampung has great potential as a farming producer of fish, among others cultivation of freshwater fish, saltwater fish, and brackish fish. Artificial feed, commonly called pellet, is the feed produced for cultivated fish ranging from freshwater payao fish and seawater. Big Hall of Marine Fisheries (BBPBL) has a medium-scale production factory that produces feed for tilapia fish, lily fish, shrimp fish, pomfret fish, and other feed. The production process at BBPBL has not yet had a standard time in the production process. It can affect processes in the production process, a less efficient working hour, and the labour force working freely. Therefore, the research wanted to design the cycle time of each subprocess of production, then obtain the normal time to determine the raw time used as standard time and determine the number of workers required for the output of production with the production standard in BBPBL. The result of this study is that the average production cycle time reached 32.18 minutes with data as much as 30. Once the cycle time is known, then the normal time obtained in the production process reached 34.67 minutes, and the raw time in the process of production reached 50.73 minutes for one cycle of the production process. Adding a workforce of 1 person to the weighing process can optimize the production process and also increase the output according to the desired target of 1,000 kg/day.